PENGARUH SENAM LANSIA TERHADAP TINGKAT INSOMNIA PADA LANSIA DI YAYASAN BINA BHAKTI SASANA TRESNAWHERDA CARITAS BEKASI - Ernauli Meliyana; Siti Maria Ulfa (Malahayati Nursing Journal, 2019)
ABSTRACT:THE INFLUENCE OF ELDERLY GYMNASTICS ON INSOMNIA LEVELS IN THE    ELDERLY IN BINA BHAKTI FOUNDATION SASANA TRESNA WHERDA CARITAS BEKASI Background: Elderly is the last stage of life cycle in humans, where the need for health promotion efforts, both promotive and preventive, in order to maintain and improve the quality of life of the elderly. The elderly is someone who has reached the age of 60 years, which is a gradual process of causing cumulative changes, such as decreased endurance and the quality of life of the elderly.Purpose: Objective is to know the influence of elderly gymnastics on insomnia level in elderly at Yayasan Bina Bhakti Sasana Tresna Wherda Caritas Bekasi.Methods:  The design used in this study was Quasi Experiment test and post test nonequivalent control group "with elderly gymnastics intervention. The population of this study is elderly living in Yayasan Bina Bhakti Sasana Tresna Wherda Caritas Bekasi, numbered 42 people in September-Maet 2017/2018. The number of samples is 20 respondents. 10 respondents of the intervention group and 10 control group respondents. Statistical test using Paired T-Test and Independent T-Test.Results: There were significant differences of influence between elderly gymnastics and progressive muscle relaxation on insomnia level in elderly at Bina Bhakti Sasana Tresna Wherda Caritas Bekasi Foundation, by using Independent Sample T-Test test obtained Sig value. (2-tailed) equal variances assumed by 0.000 0.05, Independent Test Result Sample T-Test obtained Mean group Intervention 29.80 and Mean Control group 46.10Conclusion: There were significant differences of influence between elderly gymnastics and progressive muscle relaxation on insomnia level in elderly at Bina Bhakti Sasana Tresna Wherda Caritas Bekasi Foundation. Keywords: Elderly Gymnastics, Insomnia Level, Elderly